Modified Indirect Porcine Circovirus (PCV) Type 2-Based and Recombinant Capsid Protein (ORF2)-Based Enzyme-Linked Immunosorbent Assays for Detection of Antibodies to PCV - Nawagitgul, Porntippa (American Society for Microbiology, 2002)
Postweaning multisystemic wasting syndrome of swine associated with porcine circovirus (PCV) is a recently reported and economically important disease. Simple and reliable diagnostic methods are needed for detecting antibodies to PCV type 2 (PCV2) for monitoring of PCV infection. Here, we report the development of two modified indirect enzyme-linked immunosorbent assays (ELISAs): a PCV2 ELISA based on cell-culture-propagated PCV2 and an ORF2 ELISA based on recombinant major capsid protein. PCV2 and ORF2 ELISA detected antibodies to PCV2 and the capsid protein, respectively, in sera from pigs experimentally infected with PCV2 as early as 14 and 21 days postinoculation (dpi). The kinetics of the antibody response to PCV2 and the major capsid protein were similar. Repeatability tests revealed that the coefficients of variation of positive sera within and between runs for both assays were less than 30%. To validate the assays, PCV2 and ORF2 ELISAs were performed with 783 serum samples of young and adult pigs collected from different herds in the Midwestern United States and compared with an indirect immunofluorescent assay (IIF). Six out of 60 samples collected from nursery and growing pigs in 1987 were positive by both ELISA and IIF. Compared with IIF, the diagnostic sensitivity, specificity, and accuracy of PCV2 and ORF2 ELISAs were similar (>90%). The tests showed no cross-reactivity with antibodies to porcine parvovirus and porcine reproductive and respiratory syndrome virus. There was good agreement between the two ELISAs and between the ELISAs and IIF. The availability of the two ELISAs should accelerate our understanding of the host immune response to PCV2 and facilitate the development of prevention and control strategies by elucidating the ecology of PCV2 within swine populations.